Initial Imperfection Design of Subsea Pipeline to Response Buckling Load - Junaidi, Abdul Khair; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
Oil and gas transportation in subsea operation continues to the extreme depth. Harsh environment in deep water lead to a challenge for especially pipeline design. The pipelines are operated at high pressure and high temperature in order to be able to transport the crude oil from the well to the end termination of loading. Such condition, the pipelines are subjected to axial compressive forces which will cause the pipelines to expand, consequently the pipelines tend to buckle for certain size and distance from the initial of pipeline. The sleeper is one of method to control the pipeline expansion by insertion of bar underneath the pipeline. The sleeper results initial imperfection for pipeline which forms a curvature. The magnitude of curvature is designed comply with DNV OS F101 where the design load will accommodate the combination load works on pipeline and the curvature configuration will validate by using ANSYS 14.